Approaches to the assessment and stocktaking of greenhouse gases (Eurasian Journal of Ecology, 2016)
The article considers the approaches to the assessment stocktaking and regulates greenhouse gas emissions, the ways of solving the problem of reducing greenhouse gas emissions.
Keywords: greenhouse gases; the Kyoto Protocol; greenhouse gas inventory